1992
DOI: 10.1016/s0161-6420(92)31764-6
|View full text |Cite
|
Sign up to set email alerts
|

Wolfring Dacryops

Abstract: The formation of a ductal cyst appears to require two successive, inter-related events. The first is an ongoing active secretory process, and the second is an occlusion of the duct. The sequential occurrence of these two events is forwarded as the explanation of dacryops formation. Excision using a conjunctival approach is recommended. A small strip of tarsal border should be removed with the cyst to prevent cyst rupture. The excretory ducts of the Wolfring glands exit through this area.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
63
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 24 publications
0
63
0
Order By: Relevance
“…The original theory postulated that inflammation or trauma blocked excretory ductules, leading to a mechanical dilation due to subsequent build up of secretions. 2,4 But this was not supported experimentally; obliteration of lumina caused gland atrophy and cessation of secretion with no dilation. 2 Most histological studies describe mild inflammation of the cyst wall, which is the basis for the hypothesis that a combination of periductal inflammation, hypersecretion, and impaired neuromuscular contractility of the ductules cause cyst formation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The original theory postulated that inflammation or trauma blocked excretory ductules, leading to a mechanical dilation due to subsequent build up of secretions. 2,4 But this was not supported experimentally; obliteration of lumina caused gland atrophy and cessation of secretion with no dilation. 2 Most histological studies describe mild inflammation of the cyst wall, which is the basis for the hypothesis that a combination of periductal inflammation, hypersecretion, and impaired neuromuscular contractility of the ductules cause cyst formation.…”
Section: Discussionmentioning
confidence: 99%
“…2,4 But this was not supported experimentally; obliteration of lumina caused gland atrophy and cessation of secretion with no dilation. 2 Most histological studies describe mild inflammation of the cyst wall, which is the basis for the hypothesis that a combination of periductal inflammation, hypersecretion, and impaired neuromuscular contractility of the ductules cause cyst formation. 1,4 Additionally, Weatherhead 2 suggested that an osmotic gradient produced by concentrated IgA in cystic fluid is a contributory factor for the cyst formation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of lacrimal gland cysts is believed to be related to periductal or conjunctival inflammation or trauma, which results in lacrimal gland hypersecretion and damage to duct walls with secondary obstruction and subsequent dilatation. Trachoma was suggested to be a predisposing factor in some cases 10 . Rarely, dacryops may occur simultaneously with pleomorphic adenoma or with some other neoplasms that may cause cystic dilatation of lacrimal ducts 11 …”
Section: Discussionmentioning
confidence: 99%
“…Trachoma was suggested to be a predisposing factor in some cases. 10 Rarely, dacryops may occur simultaneously with pleomorphic adenoma or with some other neoplasms that may cause cystic dilatation of lacrimal ducts. 11 Apocrine differentiation in lacrimal gland cysts is not usually mentioned as a common feature.…”
Section: Discussionmentioning
confidence: 99%